Proceedings of the 2018 ACM Conference on International Computing Education Research 2018
DOI: 10.1145/3230977.3230994
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Cognitive Career Theory to Understand Why Students Choose to Study Computer Science

Abstract: The aim of this research is to use Social Cognitive Career Theory (SCCT) to identify and understand reasons why students choose to study Computer Science (CS) at university. SCCT focuses on students' prior experience, social support, self-efficacy and outcome expectation. The research is partly motivated by the desire to increase female participation rates in CS, particularly in the UK. Policymakers can use the factors that both females and males identify as influencing their choice of studying CS to enhance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…Other studies have found that second to family, peer influence and encouragement play a major role in girls' and women's CS participation (Denner, 2011;Tillberg & Cohoon, 2005). Data from several studies identified encouragement from non-family members to be almost as important as family support, and contributed significantly more to women's decision to pursue a CS-related degree than to men (Alshahrani et al, 2018;Wang et al, 2015). Since boys are often assumed to be more interested and skilled in CS (Jane.…”
Section: The Role Of Social Support In Girls' and Boys' Participation In Csmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have found that second to family, peer influence and encouragement play a major role in girls' and women's CS participation (Denner, 2011;Tillberg & Cohoon, 2005). Data from several studies identified encouragement from non-family members to be almost as important as family support, and contributed significantly more to women's decision to pursue a CS-related degree than to men (Alshahrani et al, 2018;Wang et al, 2015). Since boys are often assumed to be more interested and skilled in CS (Jane.…”
Section: The Role Of Social Support In Girls' and Boys' Participation In Csmentioning
confidence: 99%
“…Prior studies have noted the importance of parental support in the development of children's interest in CS and in science in general (Alshahrani et al, 2018;Kekelis et al, 2005;Wang et al, 2015). A study by Stanko and Zhirosh (2017, p. 92) showed that students who choose CS as a field of study often have a family that can be characterized by "[the] ability to notice their child's interests and readiness to support a variety of interests, including interest in STEM, and IT in particular", and this is true for both girls and boys.…”
Section: Parental Attitudes Values and Support And Their Impact On Girls' And Boys' Ability Perception And Interest In Csmentioning
confidence: 99%
See 2 more Smart Citations
“…The expected benefits are most heavily centered along extrinsic motivations, including obtaining a better career or fulfilling family expectations. The most important factor influencing students to study CS, in addition to general interest and prior experience in the field, are career prospects [4,10].…”
mentioning
confidence: 99%